Axial behaviour of strengthened circular hollow reinforced concrete column with CFRP partial confinement - Ruqayyah Ismail; Raizal Saifulnaz Muhammad Rashid; Fariz Aswan Ahmad Zakwan; Hazrina Ahmad; Farzad Hejazi (Acta Polytechnica CTU Proceedings, 2022)
Circular hollow reinforced concrete column will experience deterioration due to many causes such as natural disaster, corrosion, low quality and others. Therefore, structural strengthening is required since replacing the deteriorated column is costly. Carbon fibre reinforced polymer (CFRP) confinement is one of the common method used for column strengthening. However, being a non- biodegradable material, the usage of CFRP will contribute to environmental issues. Therefore, this study investigates the effect of using partial CFRP confinement in a strengthened circular hollow reinforced concrete column. Six specimens of 2 m height with 250 mm and 110 mm for outer and inner diameter were tested. The effectiveness of partial CFRP confinement is analyzed by investigating the tested specimens’ axial and transverse displacement and strain behaviour. This study has shown that with CFRP partial confinement the strength is increased up to 44% from the unconfined circular hollow reinforced concrete column. The results of the study showed that, circular hollow reinforced concrete column with CFRP partial confinement able to enhanced the column load carrying capacity.